TRANSFORMASI SERAT PARTAWIGENA DALAM LAKON WAHYU PAKEM MAKUTHARAMA - Titin Masturoh (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
This research aims to find some answers to the questions: (1) what are the intrin- sic elements of Serat Partawigena written by KPA. Kusumadiningrat like? (2) how was Serat  Partawigena transformed into Lakon Wahyu Pakem Makutharama us- ing reception and inter-textual approaches and the intrinsic and extrinsic elements as well as their transformation were analyzed.The result of the research shows that the text contains an ethic education message to the  descendants and the next generation, especially future leaders.   The intrin- sic elements  of Serat Partawigena contains the element of plot, characterizing, setting, theme and  message.   The setting element covers place, time and atmo- sphere aspect.  The theme element includes the main theme and additional theme. The extrinsic element inSerat  Partawigena contains ethiceducation values which are the requirements for being a leader.  In addition to that, the element also con- tains seven darkness of the world which  have to be avoided by leader and seven darkness which make the body dirty.  The transformation from ofSerat Partawigena in Lakon Wahyu Pakem Makutharama exists in the pattern of plot, characterizing, characterization, setting and ethic education values. Keywords: Serat Partawigena, transformation